Communication with cancer patients: the perspective of caregivers versus non-caregivers in Iran - Naghavi, Azam; Salimi, Samaneh; Rief, Winfried; von Blanckenburg, Pia (Frontiers in Psychology, 2023)
Objective This study investigated and compared the attitudes of healthy Iranian individuals (n = 302) in forms of two groups of caregivers and non-caregivers of cancer patients about the communication with cancer patients, and their personal wish to know the diagnosis if they ever had cancer. In addition, this study aimed to identify how many participants in the caregivers’ group had spoken with their family member affected by cancer about their illness. Methods Caregivers (50.7%) and non-caregivers (49.3%) responded to two questionnaires regarding their general attitudes about communicating with cancer patients, and their willingness to know about their illness if they had cancer. Results The majority of participants (92.8%), especially in the caregiver group, agreed with the right of patients to know the diagnosis and prognosis, and also wished to know if they ever had cancer. However, around 64% of caregivers never talked about cancer with the affected patients. Conclusion Participants generally believed that patients have the right to know the diagnosis and prognosis, and they also wished to know if they ever had cancer. However, in reality many cancer patients are not included in communication sessions in Iran. Health professionals should focus on how to create a balance between medical bioethics with cultural influences on communication with patients.